Treatment of Axillary Osmidrosis by Rebalancing Skin Microecology With Lactobacillus bulgaricus - Li, Pinglu; Chen, Shuyue; Li, Ping; Xu, Dan; Tang, Xueyuan; Liao, Junlin; Xie, Hongju; Li, Gaofeng; Kuang, Yehong; Su, Juan; Tang, Shijie; Zhou, Jianda (Frontiers in Microbiology, 2022)
Corynebacterium accounts for around 20% of the armpit microbiome and plays an essential role in axillary osmidrosis (AO). In this study, the effects of Lactobacillus bulgaricus (L. bulgaricus) treatment on the microecological environment of armpits and its efficacy in the treatment of AO were investigated. A total of 10 AO patients were enrolled in this study. The patients were treated with L. bulgaricus mixed with saline on the left armpit (experimental group) and pure saline on the right armpit (control group) for 28 days. After treatment, AO severity showed a significant decrease (p = 0.013) in the experimental group compared with the control group, and the Corynebacterium abundance also showed a corresponding significant decrease (p < 0.01). Moreover, no significant variation in Staphylococcus abundance was found between these two groups. The microbe diversity is not disturbed in the treatment. Accordingly, our study demonstrates that L. bulgaricus can serve as an effective probiotic microbe for AO treatment by reducing the abundance of Corynebacterium and rebalancing the microecological environment.